IMPLEMENTASI SUPERVISI AKADEMIK GURU BERORIENTASI AKHLAKUL KARIMAH DALAM MEMBINA BEHAVIOR MENGAJAR GURU DI LEMBAGA PENDIDIKAN ISLAM - Nurdinafitri, Nurdinafitri; Muamala, Siti; Supardi, Supardi; Gunawan, Agus (STKIP Pesisir Selatan, 2025)
This study aims to analyse the implementation of academic supervision oriented towards good character in fostering teachers' teaching behaviour in educational institutions. The focus of the study includes the implementation process, supporting and inhibiting factors, and its impact on improving teachers' teaching behaviour. A qualitative approach with a case study type was used in this study, involving school/madrasah principals and teachers as research subjects. Data were collected through in-depth interviews, participatory observation, and documentation study, then analysed using the Miles and Huberman model (data reduction, data presentation, and conclusion drawing). The results show that akhlakul karimah-oriented academic supervision is implemented through a collaborative and personalised approach that integrates Islamic values into every stage of supervision. The main supporting factors are the commitment of leaders and supervisors and teachers' awareness of the importance of role models, while the inhibiting factors include time constraints and a lack of specific training. The impact is an increase in teachers' awareness of teaching ethics, professionalism based on spiritual values, and the creation of a more conducive and Islamic learning environment. This study recommends the development of a more structured supervision model with an emphasis on akhlakul karimah aspects, as well as ongoing training for supervisors and teachers.